"What shall we focus on?" – A thematic analysis of what characterizes cognitive-behavior therapy sessions with high or low quality of working alliance. (17th November 2022) - Ekeblad, Annika; Dahlman, Malene; Pio, Malin; Malmquist, Anna; Falkenström, Fredrik
Abstract : Objective: Several studies have shown that the quality of the working alliance predicts symptomatic improvement session-by-session, including in cognitive–behavioral therapy (CBT). We wanted to explore what characterizes CBT sessions with high and low alliances further using qualitative analysis. Method: Ten CBT-sessions were selected from eight patients' therapies in a larger research project on psychotherapy for patients with major depression. Five sessions were chosen from high- and five from low-alliance sessions, based on therapist- and patient-reported Working Alliance Inventory scores. Transcripts of these sessions were analyzed using thematic analysis. Results: The analysis yielded four themes, each structured into two sub-themes: Therapist style, Person in focus, Content focus, and Therapeutic direction. In contrast to low-alliance sessions, high-alliance sessions were characterized by a more exploring as opposed to expert therapist style; a focus on the patient's thoughts, feelings, and behavior, rather than a diffuse focus or a focus on other people's actions/external events; and a sense of moving forward rather than stagnation. Conclusion: Our qualitative analysis showed theoretically and clinically meaningful processes in CBT sessions of high- vs low working alliance. This method is a useful complement to quantitative within-patient analyses, to expand on the meaning of quantitative findings.